THE RELATIONSHIP BETWEEN WORK STRESS LEVELS AND HEALTH WORKERS' COMPLIANCE IN COMPLETING SURGICAL SAFETY CHECKLISTS - Nurul Aini; Muhaji; Aisyah Nur Azizah (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Patient safety in hospitals states the main priority and provides safe services, through programs that include risk assessment and identification of patient hazards. Negligence in surgical procedures has a high risk if not carried out in accordance with existing guidelines, which can lead to unwanted events or near-injuries. The use of Surgical Safety Checklist (SSC) by the surgical team and anesthesia technicians can help to minimize negligence during the operation process. Objective: Knowing the relationship between work stress and health workers' compliance in completing the SSC Method: This study used a quantitative method with a cross-sectional design. The sample consisted of 20 health workers working in the IBS room, selected through a total sampling technique. The instrument used was a questionnaire, and the data were analyzed using the Chi-Square statistical test. Results: Of the 20 respondents, most experienced high stress of 80%, with compliance of only 20%, while 80% of other health workers were not compliant. The results of the bivariate analysis using the Chi-Square test showed a significance value (p = 0.000 <0.05) with a coefficient value of -0.866. Conclusion: There is a significant relationship between work stress and health workers' compliance in filling out the SSC in the IBS room, with a p value of 0.000. This indicates that work stress affects compliance in filling out the checklist. This finding is expected to be the basis for evaluation for hospitals to improve the performance of health workers, especially anesthesiologists and surgical nurses, when implementing the SSC to maximize service quality.